2021
DOI: 10.7759/cureus.15493
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Peripheral Neuropathy Among Adult Type II Diabetes Mellitus Patients Attending a Non-communicable Disease Clinic in Rural South India

Abstract: BackgroundDiabetic peripheral neuropathy (DPN) is one of the most common microvascular complications of diabetes. Almost half of the diabetic patients develop foot ulcer as a complication of DPN during their lifetime. The aim was to estimate the prevalence and identify the risk factors of diabetic peripheral neuropathy among adult diabetes mellitus (DM) patients. MethodsA cross-sectional study was conducted among 421 type 2 DM patients attending Non-Communicable Disease (NCD) clinic in rural Puducherry through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 28 publications
4
10
0
Order By: Relevance
“…These results are comparatively higher than in other studies conducted in the Asian region. 27,28 Moreover, the DPN prevalence among the male and female T2DM patients in the current study was similar, i.e. 47.9% and 48.7%, respectively (with at least two tests being positive).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These results are comparatively higher than in other studies conducted in the Asian region. 27,28 Moreover, the DPN prevalence among the male and female T2DM patients in the current study was similar, i.e. 47.9% and 48.7%, respectively (with at least two tests being positive).…”
Section: Discussionsupporting
confidence: 63%
“…29 Other developing countries such as India (31.1%), Bangladesh (38.1%), Pakistan (39.8%) also have nearly similar values in accordance with the current study thus showing a similarity within the South Asian region. 27,28 However, developed countries such as Germany (42.2%), Korea (33.5%), USA (62.2%; national average is 28-45%) also report a higher prevalence for DPN. 30,31 In these developed countries foot ware is worn at all times in contrast to the Asian populations where foot ware is not worn indoors.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a lot of study done to evaluate the validity of these claims. 6 In this study, a comparison was be made between the clinical benefits of duloxetine for patients with DPN and the benefits of amitriptyline for these patients. Because of this, we may be able to adapt the treatment for this prevalent condition, which may ultimately result in improved patient care.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that primary care settings become more involved in the prevention and early diagnosis of DPN as the prevalence of type 2 diabetes mellitus continues to rise. 6 Antiglycemic medications and dietary management both play a crucial part in the preventive and management measures for DPN, which generally centre on glycemic control as the primary focus. The development of DPN can be delayed with the proper control of risk factors such as hypertension, hypercholesterolemia, and hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic non-communicable diseases account for more than 60% of morbidity and mortality worldwide, diabetes mellitus being one of the commonest among them 1 . According to World Health Organization more than 422 million people suffer from diabetes particularly in underprivileged and middle income countries 2 .…”
Section: Introductionmentioning
confidence: 99%